2016
DOI: 10.1177/0886260516664315
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Eating Behaviors and Sexual Harassment in Italian Male and Female University Students

Abstract: The aim of this study is to describe sexual harassment among Italian university students and analyze the relationship between harassment and disordered eating behaviors. An observational survey was conducted among university students at Trieste University (Italy) in spring 2014. Students answered an anonymous self-administered questionnaire about sexual harassment, including three domains-sexual harassment, unwanted comments on physical appearance, cyber-harassment-and disordered eating behaviors. The global s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The findings from the one longitudinal study in this review provide preliminary support for objectification theory, which states that increased SH may result in greater preoccupation with one's image, leading to greater risk of eating disorder psychopathology in the long term. This is supported by the concurrent evidence that self‐objectification, self‐surveillance, body shame, and self‐esteem were associated with the relationship between SH and eating disorder psychopathology (Funk, 2008; Harned & Fitzgerald, 2002; Holmes & Johnson, 2017; Romito et al, 2019; Wiseman & Moradi, 2010). Congruent with objectification theory, individuals who experience SH may begin to see themselves as sexual objects and compare themselves to culturally prescribed thin‐ideals.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The findings from the one longitudinal study in this review provide preliminary support for objectification theory, which states that increased SH may result in greater preoccupation with one's image, leading to greater risk of eating disorder psychopathology in the long term. This is supported by the concurrent evidence that self‐objectification, self‐surveillance, body shame, and self‐esteem were associated with the relationship between SH and eating disorder psychopathology (Funk, 2008; Harned & Fitzgerald, 2002; Holmes & Johnson, 2017; Romito et al, 2019; Wiseman & Moradi, 2010). Congruent with objectification theory, individuals who experience SH may begin to see themselves as sexual objects and compare themselves to culturally prescribed thin‐ideals.…”
Section: Discussionmentioning
confidence: 87%
“…However, and despite the limited number of published studies more generally, the results were strikingly consistent and provided clear evidence that experiences of SH are associated with eating disorder psychopathology. A statistically significant relationship was found between SH and eating disorder psychopathology in both the cross‐sectional studies and the one longitudinal study conducted (Petersen & Hyde, 2013), and even when adjusting for the potential confounding effects of sexual and physical abuse, depression and age (Buchanan et al, 2013; Casper & Lyubomirsky, 1997; Romito et al, 2019). SH was also found to be a risk correlate for weight and shape concern regardless of gender (Buchanan et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A few studies found strong associations between intimate partner violence, sexual assault and menstrual disorders, in locations as different as India, the United States and Europe [1520]. Other studies found strong links between sexual harassment, mental health outcomes [21] and eating disorders [22,23]. However, to our knowledge, little attention has been paid to the impact of sexual harassment on menstrual disorders.…”
Section: Introductionmentioning
confidence: 99%